Identification of ST1 reveals a selection involving hitchhiking of seed morphology and oil content during soybean domestication. Issue 6 (5th March 2022) - Li, Jun; Zhang, Yuhang; Ma, Ruirui; Huang, Wenxuan; Hou, Jingjing; Fang, Chao; Wang, Lingshuang; Yuan, Zhihui; Sun, Qun; Dong, Xuehui; Hou, Yufeng; Wang, Ying; et al.
Summary: Seed morphology and quality of cultivated soybean ( Glycine max ) have changed dramatically during domestication from their wild relatives, but their relationship to selection is poorly understood. Here, we describe a semi‐dominant locus, ST1 ( Seed Thickness 1 ), affecting seed thickness and encoding a UDP‐D‐glucuronate 4‐epimerase, which catalyses UDP‐galacturonic acid production and promotes pectin biosynthesis. Interestingly, this morphological change concurrently boosted seed oil content, which, along with up‐regulation of glycolysis biosynthesis modulated by ST1, enabled soybean to become a staple oil crop. Strikingly, ST1 and an inversion controlling seed coat colour formed part of a single selective sweep. Structural variation analysis of the region surrounding ST1 shows that the critical mutation in ST1 existed in earlier wild relatives of soybean and the region containing ST1 subsequently underwent an inversion, which was followed by successive selection for both traits through hitchhiking during selection for seed coat colour. Together, these results provide direct evidence that simultaneously variation for seed morphology and quality occurred earlier than variation for seed coat colour during soybean domestication. The identification of ST1 thus sheds light on a crucial phase of human empirical selection in soybeans and provides evidence that our ancestors improved soybean based on taste.